IDENTIFIKASI ASPEK HUKUM DALAM HAL DIRUMAHKANNYA KARYAWAN INDUSTRI PARIWISATA (HOTEL) SEBAGAI DAMPAK PANDEMI CORONA - Suarsana Ariesta, I Putu Agus; Bagus Widiantara, I Gusti Agung (Akademi Komunitas MAPINDO, 2020)
The world health organization (WHO) had designated the outbreak of the corona virus as a pandemic, which started in the Chinese city of Wuhan. The corona pandemic has an impact on the tourism industry sector around the world, including in Badung Regency, Bali. In the tourism industry there was also a tourist accommodation component, including hotels. The existence of hotels in Bali has contributed greatly to the absorption of workers who came from Balinese residents and residents outside Bali and even foreign workers, which greatly impacts the economy of the community and regional income. Entrepreneurs in the tourism sector are forced to lay off their employees. Especially with the application of Lock Down which is applied in the international world. The implementation of domestic policies will certainly have an impact on employers, employees and local governments, in this case the Badung Regency Government. This policy requires assistance from the government, the Department of Industry and Manpower, as a mediator to get an agreement related to employee dismissal decisions. For this reason, the act of laying off employees is an act of salvation for both the employer and the employee side. Therefore, in this study it is necessary to know the legal aspects or basis and procedures for their implementation that must be taken in the face of the corona pandemic. Keywords: legal aspects, housing, employees, corona pandemic.